2010
DOI: 10.1105/tpc.109.068627
|View full text |Cite
|
Sign up to set email alerts
|

VERDANDIIs a Direct Target of the MADS Domain Ovule Identity Complex and Affects Embryo Sac Differentiation inArabidopsis 

Abstract: In Arabidopsis thaliana, the three MADS box genes SEEDSTICK (STK), SHATTERPROOF1 (SHP1), and SHP2 redundantly regulate ovule development. Protein interaction studies have shown that a multimeric complex composed of the ovule identity proteins together with the SEPALLATA MADS domain proteins is necessary to determine ovule identity. Despite the extensive knowledge that has become available about these MADS domain transcription factors, little is known regarding the genes that they regulate. Here, we show that S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
121
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(126 citation statements)
references
References 86 publications
(111 reference statements)
5
121
0
Order By: Relevance
“…Especially CArG box 1 and 3 seem to be most important for the establishment of loop formation. This is in agreement with ChIP experiments that showed that in vivo STK and SEP3 only use CArG box 1 and 3 in the VDD promoter (Matias-Hernandez et al, 2010). Interestingly, when we tested by TPM assays the VDD promoter with a single CArG box deletion, loop formation was only observed when the CArG box 2 was deleted.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Especially CArG box 1 and 3 seem to be most important for the establishment of loop formation. This is in agreement with ChIP experiments that showed that in vivo STK and SEP3 only use CArG box 1 and 3 in the VDD promoter (Matias-Hernandez et al, 2010). Interestingly, when we tested by TPM assays the VDD promoter with a single CArG box deletion, loop formation was only observed when the CArG box 2 was deleted.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, they regulate the expression of VDD through direct binding to its promoter region (Favaro et al, 2003;Matias-Hernandez et al, 2010). The VDD promoter region contains three CArG boxes within the region 1000 bp upstream of the ATG start codon ( Figure 1A; Matias-Hernandez et al, 2010). Cooperative binding of the tetramers (composed of two SEP3-STK heterodimers) to two of the three adjacent CArG boxes would induce the formation of loops within the promoter region, which might have important regulatory functions.…”
Section: Sep3mentioning
confidence: 99%
See 3 more Smart Citations